Analisis Beberapa Faktor Yang Berpengaruh terhadap Penggunaan Informasi Akuntansi pada Usaha Kecil dan Menengah - Seftianita Nirmalasari (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2020)
Small and medium enterprises are the largest economic community in Indonesia and are one of the factors of economic growth after the economic crisis. In addition, small and medium-sized businesses open up quite large job opportunities. Accounting information is one of the important things for the development of small and medium enterprises. Soo this research, the writer wants to analyze more clearly several factors that influence the use of accounting information in small and medium enterprises in the Pudak city Gresik. The population in this study was the owners/managers of small and medium enterprises in Pudak city Gresik. The number of samples studied was 86 respondents. The sampling method was used a random sampling technique. The data analysis used multiple linear regression analysis with the help of the SPSS program. The results of data analysis show that business scale, business age, accounting knowledge, and accounting training are found to have a positive and significant effect on the use of accounting information in small and medium enterprises in the Pudak city Gresik.